The Carbon Fiber-Reinforced Plastic Project - Mohamed, Prof. Ts. Dr. Saiful Bahri; Muhamad @ Mohd Saufi, Ts. Dr. Martin; Ab Rashid, Prof. Madya Dr. Radzuwan (Springer Verlag, 2019)
Activities in a research project may be structured into a series of tasks. Each task should be clearly defined and understood to ensure the possibility of introducing effective strategies and concepts for experimental design